The British world : diaspora, culture, and identity - Bridge, Carl; Fedorowich, Kent, 1959- (F. Cass, 2003)
This collection of essays is based upon the assumption that the British Empire was held together not merely by ties of trade and defence, but by a shared sense of British identity that linked British communities around the globe.
"This group of studies first appeared as a special issue of The Journal of imperial and Commonwealth history (ISSN 0308-6534), vol. 31, no. 2, May 2003, published by Frank Cass"--Title page verso
Keywords: Great Britain -- Colonies -- History.; Great Britain -- Colonies -- Emigration and immigration -- History.; Great Britain -- Emigration and immigration -- History.; Group identity -- Great Britain -- Colonies -- History.; Commonwealth countries -- Civilization.; National characteristics, British.; Great Britain -- Civilization.; British.; Grande-Bretagne -- Colonies -- Histoire.; Grande-Bretagne -- Colonies -- Émigration et immigration -- Histoire.; Pays du Commonwealth -- Civilisation.; Britanniques.; Grande-Bretagne -- Civilisation.; HISTORY -- World.; British; British colonies; Civilization; Emigration and immigration; Group identity; National characteristics, British; Commonwealth countries; Great Britain; Emigratie.; Culturele identiteit.; Nationale identiteit.; Electronic books.; History